Beberapa Aspek Pertumbuhan Lamun Enhalus acoroides (Linn. F) Royle di Pulau Barrang Lompo Makassar - Supriadi Supriadi; Dedi Soedharma; Richardus F Kaswadji (Fakultas Biologi | Universitas Jenderal Soedirman, 2006)
A study has been conducted to investigate some aspects related to seagrass Enhalus acoroides growth in Barrang Lompo Island Makassar by using a modified tagging method. Tagging was applied monthly to 20 seagrass stands for seven months with weekly observations. The results showed that Enhalus acoroides growth had a quadratic pattern and was strongly affected by exposed environmental condition, turbidity, nutrient, and temperature.